2011
DOI: 10.1016/j.topol.2011.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Small loop spaces and covering theory of non-homotopically Hausdorff spaces

Abstract: In this paper we devote to spaces that are not homotopically hausdorff and study their covering spaces. We introduce the notion of small covering and prove that every small covering of X is the universal covering in categorical sense. Also, we introduce the notion of semi-locally small loop space which is the necessary and sufficient condition for existence of universal cover for non-homotopically hausdorff spaces, equivalently existence of small covering spaces. Also, we prove that for semi-locally small loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…Except for the uniform universal cover, we will not need or use any of the recent, non-traditional generalizations of universal covers that relax the evenly covered property (cf. [5], [6], [15], [20]). When we use the uniform universal cover, it will always be explicitly referenced as such, so no confusion should result.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for the uniform universal cover, we will not need or use any of the recent, non-traditional generalizations of universal covers that relax the evenly covered property (cf. [5], [6], [15], [20]). When we use the uniform universal cover, it will always be explicitly referenced as such, so no confusion should result.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In particular, π cl (X) contains what Pakdaman, Torabi, and Mashayekhy call in [20] the SG-subgroup. This is the subgroup π sg 1 (X) ⊂ π 1 (X) generated by all small loop lollipops, or path loops of the form αβα −1 , where α is a path beginning at * and β is a small path loop based at α(1).…”
Section: The Revised Fundamental Groupmentioning
confidence: 97%
“…As it is shown in [11], there exist special subgroups of fundamental groups of non-homotopically Hausdorff spaces which have great influence on their coverings. In fact, if a space X is not homotopically Hausdorff, then there exists x ∈ X and a nontrivial loop in X based at x which is homotopic to a loop in every neighborhood U of x (see [8] for the definition of homotopically Hausdorffness).…”
Section: Introductionmentioning
confidence: 99%
“…In general, various points of X have different small loop groups and hence in order to have a subgroup independent of the base point, Virk [14] introduced the SG (small generated) subgroup, denoted by π sg 1 (X, x), as the subgroup generated by the following set {[α * β * α −1 ] | [β] ∈ π s 1 (X, α(1)), α ∈ P (X, x)}, where P (X, x) is the space of all paths from I into X with initial point x. Virk [14] calls a space X a small loop space if π s 1 (X, x) = π 1 (X, x) = 1 for all x ∈ X. The authors [11] showed that for a covering p : ( X,x) → (X, x) the following relations hold: π s 1 (X, x) ≤ π sg 1 (X, x) ≤ p * π 1 ( X,x). It should be noted that by a result of Spanier [13, §2.5 Lemma 11] one has π sg 1 (X, x) ≤ π(U, x) ≤ p * π 1 ( X,x), ( * )…”
Section: Introductionmentioning
confidence: 99%
“…Also, the authors [10,13] studied the covering theory of non-homotopically Hausdorff spaces. Accordingly, we would like to study coverings of non-homotopically path Hausdorff spaces and investigate the topology type of their fundamental group and their universal covering spaces.…”
Section: Introductionmentioning
confidence: 99%